Effect of stem cell source on outcomes after unrelated donor transplantation in severe aplastic anemia - Eapen, Mary (American Society of Hematology, 2011)
Outcome after unrelated donor bone marrow (BM) transplantation for severe aplastic anemia (SAA) has improved, with survival rates now approximately 75%. Increasing use of peripheral blood stem and progenitor cells (PBPCs) instead of BM as a graft source prompted us to compare outcomes of PBPC and BM transplantation for SAA. We studied 296 patients receiving either BM (n = 225) or PBPC (n = 71) from unrelated donors matched at human leukocyte antigen-A, -B, -C, -DRB1. Hematopoietic recovery was similar after PBPC and BM transplantation. Grade 2 to 4 acute graft-versus-host disease risks were higher after transplantation of PBPC compared with BM (hazard ratio = 1.68, P = .02; 48% vs 31%). Chronic graft-versus-host disease risks were not significantly different after adjusting for age at transplantation (hazard ratio = 1.39, P = .14). Mortality risks, independent of age, were higher after PBPC compared with BM transplantation (hazard ratio = 1.62, P = .04; 76% vs 61%). These data indicate that BM is the preferred graft source for unrelated donor transplantation in SAA.